A Case Report: Combined Sciatic Nerve and Lumbar Plexus Nerve Block in A Patient with Acute Decompensated Heart Failure Undergoing Lower Extremity Surgical Debridement - Tantri, Irma Lusiana; Saroso, Natalia Frederika Darmawan Adji; Domini, Marielle Ancilla; Wiwing, Veronica (Fakultas Kedokteran Universitas Pelita Harapan, 2023)
Background: Peripheral nerve block for lower extremity surgeries requires a minimum of two block injections. Although the combination of the lumbar plexus block and the sciatica block is a procedure that requires large doses of local anesthetic, which may induce cardiotoxicity, a recent study suggests that change in the hemodynamic system is not clinically significant.Case Description: We report a case of a 53-year-old male presenting with a worsened shortness of breath two days before hospital admission. He also experienced a sudden high fever and pain on his right thigh. The patient had a history of Heart Failure (EF 28%) and Congestive liver disease and was diagnosed with right femur cellulitis with right phlegmon. Surgical debridement was planned to treat sepsis. Right lumbar plexus block and right sciatica block were performed as surgical anesthesia. The surgery duration was one hour, and the patient was transferred to the PACU. The patient was treated in ICU before being admitted to the general ward and was discharged on day three post-surgery.Conclusion: The combination of Sciatic nerve and lumbar plexus nerve block is an effective anesthesia and analgesia technique for lower limb surgery in individuals with a severe heart condition.